2011
DOI: 10.1016/j.exer.2010.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Mitogen-activated protein kinase phosphatase-1 (MKP-1) in retinal ischemic preconditioning

Abstract: We previously described the phenomenon of retinal ischemic preconditioning (IPC) and we have shown the role of various signaling proteins in the protective pathways, including the mitogen-activated protein kinase p38. In this study we examined the role in IPC of mitogen-activated protein kinase phosphatase-1 (MKP-1), which inactivates p38. Ischemia was produced by elevation of intraocular pressure above systolic arterial blood pressure in adult Wistar rats. Preconditioning was produced by transient retinal isc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 39 publications
(73 reference statements)
1
17
0
Order By: Relevance
“…Activation (phosphorylation) of Akt is involved in cell survival while JNK and Erk1/2 are stress-activated kinases that can eventually lead to apoptosis. For example, MAPKs are activated by ischemia [51], peroxide induced RPE cell death [52], and hyperglycemia-induced pro-inflammatory responses by retinal Müller glia that is regulated by the receptor for advanced glycation end-products (RAGE) [53]. In the present studies induction of signaling was observed in AK-SMAA-GFR-hAR mice and their induction was reduced by ARI treatment.…”
Section: Discussionmentioning
confidence: 47%
“…Activation (phosphorylation) of Akt is involved in cell survival while JNK and Erk1/2 are stress-activated kinases that can eventually lead to apoptosis. For example, MAPKs are activated by ischemia [51], peroxide induced RPE cell death [52], and hyperglycemia-induced pro-inflammatory responses by retinal Müller glia that is regulated by the receptor for advanced glycation end-products (RAGE) [53]. In the present studies induction of signaling was observed in AK-SMAA-GFR-hAR mice and their induction was reduced by ARI treatment.…”
Section: Discussionmentioning
confidence: 47%
“…This results in so-called "ischaemic preconditioning" of the tissue (a term that is here preferred to "ischaemic tolerance"). Thus, at least for a period of several days and through a variety of neuroprotective and ATP conserving mechanisms, preconditioned neurons are more resistant to the potential deleterious effect of a subsequent anoxic insult that would otherwise be rapidly lethal for the cells (Dreixler et al, 2011). The ophthalmic manifestations of such a reduced susceptibility to ischaemia aren't precisely known; as well as prolonging the inner retinal survival time by limiting the intracellular accumulation of Ca þþ and other mechanisms (Tauskela et al, 2012), a reduction in the degree or extent of ischaemic swelling, or in the volume of axoplasmic debris accumulating, may follow.…”
Section: Prehistory Of Sublethal Ischaemia or Hypoxaemiamentioning
confidence: 99%
“…Several studies have demonstrated that ischemic conditioning protected retinal function and histology from ischemia-reperfusion injury, when applied before experimental retinal ischemia (preconditioning) and after (postconditioning) reperfusion (Fernandez et al, 2009 b ;Dreixler et al, 2011 a , b ). The preconditioning and postconditioning initiate and potentiate endogenous protective mechanisms, which subsequently diminish reperfusion injury through neutralizing ROS (Zhang et al, 2002 ;Obolensky et al, 2008 ).…”
mentioning
confidence: 99%